Self-absorption and technique: recent contributions for a systematic interpretation of Ortega y Gasset’s work - Núñez Ladevéze, Luis; Álvarez de Mon, Ignacio; Núñez Canal, Margarita (Universidad CEU San Pablo, 2022)
The digitised edition of the Complete Works(Obras Completas)of the Centre for Orteguian Studies of the Ortega y Gasset Foundation (Centro de Estudios Orteguianos de la Fundación José Ortega y Gasset), in which a meticulous work method has been used to chronologically organise his philosophical and journalistic endeavours, has served as an effective platform for renewed interest in his legacy. Ortega y Gasset forecasted several highly important phenomena, the importance of which can now be verified, such as the accelerated advance of technology, Europe’s lower profile as a world leader, transfer of the revolt of the masses to social networks, and the close proximity of the planet due to advances in communication. The fruition of these prognostications and the meticulousness of the edition have created renewed interest in studying his work, which has been reflected in the recent publication of writings that highlight the foresighted originality of Orteguian philosophy. These works concur in emphasising that the core essence that gives meaning to Ortega’s work as a whole is to be found in his philosophy of technique. This paper analyses a new approach that updates the validity of the Madrid-born philosopher’s vision by focusing on his concept of technology.
Keywords: 72 Filosofía; Philosophy of the technique; technology; mass culture; robotics